Effectiveness Of The Use Google Meet Application In Learning Biology At Class Xi Students Of Sma Negeri 1 Pematang Bandar - Risjunardi Damanik; Marlindoaman Saragih (Jurnal Info Sains : Informatika dan Sains, 2023)
This study aims to measure the effectiveness of using Google Meet in online learning on the Excretion System material. This study measures how student learning outcomes using Google Meet. The method used is a descriptive qualitative research method where researchers see learning outcomes before doing learning before and after learning with Google Meet. To measure the effectiveness of using Google Meet, researchers used Observation sheets, Documentation studies and learning outcomes tests. The data from the three instruments were tested first to students outside the sample, this was done to see the validity of the instrument. The data analysis technique used normality test, homogeneity test and t-test. The normality test was carried out using the Kolmogorof Smirnov test with the help of SPSS 26. The normality test was the result of the Asymp value pretest. Sig (2-tailed) 0.319 > 0.05 and the posttest result is Asymp value. Sig (2-tailed) 0.19 > 0.05, it can be seen that the data on student learning outcomes is normally distributed. As for the homogeneity test, it can be seen that the student learning outcomes data have a homogeneous variant because the significance value is 0.71, so 0.71 > 0.05. Hypothesis testing was carried out using the paired t-test using SPSS 26. The results of the paired t-test were the sig. (2-tailed) 0.000 < 0.05 so it can be concluded that H0 is rejected and Ha is accepted, which means that there is an effective use of Google Meet in online learning to improve student learning outcomes in Class XI SMA Negeri 1 Pematang Bandar.